Studi Eksperimental: Pengaruh Sudut Kemiringan Dan Massa Terhadap Gerak Linier Kereta Dinamika - Alya Hanifah Wardani; Musbar Nurul Ilyas; Kristina Nurdiyani; Rufaidah Kamilia Ahsani (Lembaga Pengembangan Kinerja Dosen, 2024)
Finding out how mass and slope affect the linear motion of dynamic trains is the goal of this investigation. To learn more about how variations in reach and tilt angle can impact an object's acceleration and speed, a variety of tests were conducted in this experiment with varying reach and tilt angle modifications. According to study findings, an object's speed and acceleration are greatly impacted by changes in its size. The object's speed increases in proportion to its mass because larger masses result in faster acceleration. The object's speed is, however, also impacted by variations in the track's inclination angle. An object moves more quickly at a larger tilt angle than it does at a smaller tilt angle. These conclusions are confirmed by calculations that demonstrate how an object's size affects its success. Further developments in this field can be based on the study's results, as they enhance our comprehension of the factors influencing linear motion in dynamic trains.